Progressive Pseudorheumatoid Dysplasia of Childhood (PPRD)—A Case Series with Recurrent c.740_741del Variant - Nilay, Mayank; Rawool, Anup; Mandal, Kausik (Journal of Pediatric Genetics, 2021)
Progressive pseudorheumatoid dysplasia (PPRD) is an autosomal recessive arthropathy, affecting school-aged children. It is characterized by progressive degeneration of the articular cartilage. The majority of the pathogenic variations are found in exon 2, exon 4, and exon 5 of the putative gene, CCN6 (WISP3). Three unrelated individuals with clinical diagnosis of PPD were included in this study. Detailed clinicoradiological evaluation was attempted with brief literature review. Exome sequencing was performed in all three cases. All the pathogenic variations detected in our cohort were located in exons 2 and 4 of WISP3 gene. Though the clinicoradiological features are already well described, this study in north India highlights the occurrence of a recurring pathogenic variant. The c.740_741del variant was a recurrent pathogenic variant seen in all three patients in this cohort. This may be a common pathogenic variant in the North Indian population; however, a larger cohort needs to be studied before drawing final conclusions. A proper molecular diagnosis is a must to end the diagnostic odyssey, safeguarding patients with PPRD from unnecessary use of drugs like corticosteroids.
Keywords: mutation; CCN6; skeletal dysplasia; interphalangeal joint; compound heterozygous